The Effectiveness of the Screening Method with Significant (TBC Response Application) in Improving the Networking of Suspects and Case Detection Rate (CDR) Tuberculosis in Sumenep District in 2021 - Yuly Peristiowati; Herman Pratikto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Tuberculosis is a contagious infectious disease caused by Mycobacterium tuberculosis, which can attack the lungs and other organs. Until now, it is still a public health problem in the world that causes high morbidity, disability, and death, so it is necessary to carry out integrated, comprehensive and sustainable prevention efforts and involve all parties. The purpose of this study was to identify the achievements of screening suspects and CDR TB using SIGAP, identify the achievements of screening suspects and CDR TB using a manual questionnaire and analyze the effectiveness of screening with SIGAP and manuals to increase the achievement of screening suspects and CDR TB in Sumenep district. This study is a quasi-experimental design with a non-equivalent control group design with pretest and post-test. This research was conducted in 22 Puskesmas in Sumenep Regency, 430 samples were taken which were divided into 2 groups. Independent t test analysis to see the difference between the two screening methods. then the data were analyzed using the Mann Whitney test. The results showed that the SIGAP method has a higher value than the Manual (251.85 > 179.15) in screening suspects, and the SIGAP method has a higher value than the Manual method (250.50 > 180.50), in increasing the achievement of the Case Detection Rate of Tubercolosis better. . This shows that there is an effect of the SIGAP screening method in increasing the Suspect and Case Detection Rate Tuberculosis achievement in Sumenep Regency. It is hoped that the results of this study can become the basis for the need for policies from the health department and local governments to support the implementation of the SIGAP application and develop a screening module that makes it easier for individual users so that they can self-screen.